Governance strategies for end-of-life electric vehicle battery recycling in China: A tripartite evolutionary game analysis - Wei, Lang; Wang, Cuixia; Li, Yaqin (Frontiers in Environmental Science, 2022)
End-of-life (EOL) electric vehicle (EV) batteries has both economic and environmental benefits if recycled in an environmentally friendly manner while may cause environmental pollution if treated improperly. China is currently working hard to promote the development of circular economy by EOL EV batteries recycling. However, conflicts of interest among electric vehicle manufacturers (EVMs), consumers and the government often hinder the efficient recycling. This paper constructs a tripartite evolutionary game model under the condition of bounded rationality, analyzes the evolutionary stability strategy of three participants, and combines with numerical simulation to explore the feasible governance strategies of EOL EV batteries recycling. The results shown that four evolutionary stable strategies (ESSs) correspond to the three stages of EOL EV batteries recycling industry: early stage, development stage and maturity stage. In the early stage, the punishment strategy is more critical to motivate EVMs and consumers to actively participate in batteries recycling. The subsidy mechanisms can influence the strategic choices of the three participants, but the excessive subsidy is not conducive to the sustainable development of EOL EV batteries industry. Besides, when the industry matures, the government will gradually decrease intervention, thereby realizing the development path of EOL EV batteries recycling from exogenous government supervision to endogenous profit drive.